PENINGKATAN HASIL BELAJAR PASSING BAWAH BOLA VOLI MENGGUNAKAN BOLA SPONS - Harahap, Hasan Ashari (Jurnal Kajian Pembelajaran dan Keilmuan, 2022)
The Problem in this study is whether there is an increase in Volleyball Bottom Passing Learning Outcomes Using Sponge Ball Class VIIA SMPN 4 Sungai Raya, Kubu Raya Regency for the Academic Year 2021-2022. The method used in this research uses a classroom action research approach because to improve the learning process through a cycle that includes planning, implementation, observation and reflection, it shows that in the first cycle the percentage of students"™ completeness is only 71,79%, namely 28 students from 39 person. As for the incomplete, there are 28, 21%, namely as many as 11 students from 39 people. This is then a note and reflection for improvement in cycle II. In Cycle II, the percentage of students"™ completeness was 84, 61%, namely 33 students from 39 people. As for the percentage of incomplete, there are 15, 39% or as many as 6 students from 39 people. This is what then becomes a note and reflection that must be strengthened in order to be able to contribute to the volleyball underhand passing.